Daily fitness and nutrition journal (McGraw-Hill, 2005)
This logbook helps students track their diet and exercise programs. It serves as a diary to help students monitor their behaviors. It can be packaged with any McGraw-Hill textbook for a small additional fee. It comes free with Fit and Well by Fahey et al.